Predictors for the prescription of albuterol in infants hospitalized for viral bronchiolitis (2020)
Introduction and Objectives Despite the recommendation against routine use of inhaled bronchodilators in infants with viral bronchiolitis given in the main clinical practice guidelines (CPGs) on viral bronchiolitis, albuterol is widely prescribed to patients with this disease. The aim of this study was to identify predictors of prescription of albuterol in a population of infants hospitalized for viral bronchiolitis. Material and Methods An analytical cross-sectional study performed during the period from March 2014 to August 2015, in a random sample of patients <2 years old hospitalized in the Fundacion Hospital La Misericordia, a hospital located in Bogota, Colombia. After reviewing the electronic medical records, we collected demographic, clinical, and disease-related information, including prescription of albuterol at any time during the course of hospitalization as the outcome variable. Results For a total of 1365 study participants, 1042 (76.3%) were prescribed with albuterol therapy. After controlling for potential confounders, it was found that age (OR 1.11; CI 95% 1.08–1.15; p < 0.001), and a prolonged length of stay (LOS) (OR 1.93; CI 95% 1.44–2.60; p < 0.001) were independent predictors of prescription of albuterol in our sample of patients. By contrast, albuterol prescription was less likely in the post-guideline assessment period (OR 0.41; CI 95% 0.31–0.54; p < 0.001), and in infants with RSV isolation (OR 0.71; CI 95% 0.52–0.97; p = 0.035). Conclusions Albuterol was highly prescribed in our population of inpatients with the disease. The independent predictors of prescription of albuterol in our sample of patients were age, implementation of a CPG on viral bronchiolitis, RSV isolation, and LOS.